"Mole removal" on Instagram Hashtags: A Cross-sectional Analysis: Nevus Treatment Methods on Instagram - GUDER, SEMİH; Guder, Semih; Güder, Hüsna (My University, 2022)
Introduction: With the increase in the use of social media, there is a steady increase in demand for medical, surgical, and cosmetic procedures. Dermatologists and other physicians are leaving their cosmetic practice to non-physician service providers to keep up with the growing demand for cosmetic procedures. Objectives: To examine the gender, professions, and the method of nevi treatment of the profiles using #bensilme and #moleremoval hashtags on Instagram and to investigate the extent of cosmetic procedures comparing Turkey's situation with other countries. Methods: In Instagram, the most frequently used hashtags about nevus treatment were scanned by two dermatologists. We recorded profession, gender, country of origin, and the treatment method of nevi of profiles sharing the related posts. Results: The countries with the highest share of the #moleremoval hashtag were the United Kingdom (15%), India (12%), and the United States of America (10.5%), and the proportion of physicians in these countries was 16.7%, 100%, and 71.4%, respectively. In the non-physician group, plasma pen method in our country is the most used method (Turkey: 97.9%, world: 75% respectively), but the use of radiofrequency cautery (world: 12.5%, Turkey: 1% respectively) and cryo pen (world: 7.5%, Turkey: 0.0%) methods were significantly more abroad. Conclusions: We demonstrated that non-physicians mostly perform nevus destruction procedures. Physicians must use social media more actively to share educational, quality, and accurate information. We suggest that the hashtags used by physicians in their social media posts should be chosen from the words used in the folk language.
Keywords: Instagram; Nevus treatment; Plasma energy devices; Cauterization; Social media; Non-physicians practice